(untitled) (Damascus University Journal of arts and humanities sciences, 2022)
This research paper is a feminist-postcolonial study of Wanjiru’s identity crisis as an inevitable outcome of double colonialization in Ngugi wa Thiong’o’s “Minutes of Glory.” The colonial enterprise and the patriarchal society are accomplices who have subdued Wanjiru’s body and mind leading to the fragmentation of her identity. There are four manifestations of her identity crisis. The first one is transforming her body into a sexual object that satisfies male desire. A seductive woman adopting the “white” standards of beauty is capable of alluring wealthy men to the bars. Secondly, Wanjiru strives to construct an identity that is a replica of the white colonizer by changing her name and bleaching her skin. In addition to objectification and mimicry, she attempts to elude her alienation by establishing a middle space where she can feel a sense of belonging. She attempts to construct this space between the city and countryside, being a maid and working as a prostitute and wanting to build a relationship with a man who is both a client and a supposed “lover.” The last manifestation is her resistance to the fixed image of female colonial subjects. She uses silence and her body as weapons of resistance. In other words, Wanjiru resembles most female colonial subjects who attempt to redress the wounds of their broken self under the oppressive domination of the colonial powers and patriarchy.